Implementation of a Degassing System at the MSW Landfill - Shkileva, Anna (Civil Engineering Journal, 2021)
Aitolo-Akarnania prefecture, western Greece, is an area with strong earthquakes and large active fault systems. The most, the second half of the 20th century was characterized for the world community by the aggravation of the environmental problem. Anthropogenic pollution of the environment with the growth of industrial and agricultural production, the growth of cities, the size of the population, the volume of their consumption clearly indicates that the world community is on the brink of an abyss. The destruction of forests, pollution of water bodies, degradation of soil, flora and fauna, the emergence of new diseases clearly shows that if urgent and drastic measures are not taken to save the environment, the life of future generations is problematic. In Russia, as in other countries of the world, the amount of solid household waste has been sharply increasing lately. Therefore, their processing and disposal is becoming an increasingly urgent problem that requires the adoption of complex solutions. At the same time, overcrowded and smoking landfills, as well as formed unauthorized landfills are the main sources of environmental pollution. Landfills of solid municipal waste not only cause an epidemiological hazard, but due to the anaerobic decomposition of organic waste, causing the formation of explosive biogas, become a powerful source of biological pollution. Biogas generated at MSW landfills in the process of decomposition has a toxic effect on living organisms, contributes to the outbreak of fires, and is a source of unpleasant odors. This problem must be solved by introducing a degassing system at municipal solid waste landfills already at the stage of their operation. The proposed degassing system at the MSW landfill is aimed at reducing the negative impact of biogas on the environment.Â Doi: 10.28991/cej-2021-03091706 Full Text: PDF